Photocatalytic H-2 evolution from water-methanol mixtures on InGaO3(ZnO)(m) with an anisotropic layered structure modified with CuO and NiO cocatalysts - Narendranath, Soumya B.; Thekkeparambil, Saranya V.; George, Leena; Thundiyil, Shibin; Devi, R. Nandini (Journal of Molecular Catalysis A-Chemical, 2016)
InGaO3(ZnO)(m) series of oxides is found to be active for photocatalytic H-2 evolution from water-methanol mixtures. The structure of this series is highly anisotropic with InO6 octahedral layers sandwiching Ga/ZnOn polyhedra. The structural anisotropy in which the conducting layer is spatially separated from the charge generation sites may help in suppressing charge recombination and consequently enhance catalytic activity. The band gaps of the series obtained from absorption spectra are above 3.6 eV and hence they are not active under visible light irradiation. H-2 evolution is considerably enhanced under UV light on employing NiO as cocatalyst due to facile electron transfer from InGaO3(ZnO)(m). to NiO. However, when CuO is used as cocatalyst, visible light activity could be brought out. Due to the very low band gap of CuO, it can act as a sensitizer absorbing in visible light. The band positions become conducive for H-2 evolution due to band alignments consequent to electron accumulation in CuO conduction band. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: InGaO3(ZnO)(m); photocatalytic water splitting; visible light; XPS; XRD